(3HjGf GdCMcGe aj GdNQbI hGdSLGOI hGdCYdGe heG EQJcHg ef GdCbhGd hGdCaYGd eTGjN GdChgGes - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s ((3YHO GdhgGH Hf SdjeGf GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO CjgG GdSGdc HfaSg GdMGce Hhgeg GdebJOi HQCjg ai EJNGP SLGOJg hNQbJg hYdeg aGYde Cf GdSLGOg hGdNQbI hGdYde ef ETGQGJ GdCFeI GdeJbOejf GdegJOjf s
(3BNQgG (B:s
(3hGddg JYGdi GdeSFhd ai GdJhHI hGdKHGJ Ydi GdcJGH hGdSfI Edi GdeeGJ hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg NjQ eGV hBJ eG OGeJ GdSeGhGJ hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs